Advanced thermally drawn multimaterial fibers: structure-enabled functionalities - Wang, Zhe (2022)
Thermally drawn multimaterial fibers have experienced rapid development in the past two decades owing to the high scalability, uniformity, and material and structure compatibility of the thermal drawing technique. This article reviews various multimaterial fibers based on different functional structures and their applications in disparate fields. We start from the functional structures achieved in optical fibers developed in the early stage of thermally drawn fibers. Subsequently, we introduce both typical functional structures and unique structures created in multimaterial fibers for varying applications. Next, we present the early attempts in breaking the axial symmetric structures of thermally drawn fibers for extended functionalities. Additionally, we summarize the current progress on creating surface structures on thermally drawn fibers. Finally, we provide an outlook for this trending topic towards wearable devices and smart textiles.